Akibat Hukum Jual Beli Tanah Warisan Tanpa Persetujuan Ahli Waris - Feby Adelia Parhusip; Wida Bonor Gultom; Muhammad Yoga Pratama; Sri Hadiningrum (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Islamic inheritance law is one of the rules that regulates humans and humans in matters of inheritance (inheritance). This law regulates the transfer of assets from deceased people to living people with detailed calculations and distribution. The aim of this research is to determine the legal consequences of buying and selling inherited land without the consent of the heirs. In this research the author uses Normative Law research, which is carried out by examining and analyzing legal regulations with legal issues in their consistency with existing principles. This type of research is a type of library research, which relies on the study and study of texts. The research results show that in Islamic law, land inheritance does not yet exist has been circulated and is prohibited from being sold because it still belongs to other heirs. If all heirs agree to the sale and purchase, it can be traded, if not it is considered illegal and revoked. Legal protection for buyers of inherited land that is not distributed is that they can file a civil lawsuit against the seller and the Notary/PPAT (official with the authority to make deeds) who has made the sales agreement.